Pengaruh Environmental Performance dan Material Flow Cost Accounting Terhadap Sustainable Development: pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Risma Aulia Putri; Lilis Lasmini; Rohma Septiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increase in industrial activities has impacts on the environment, as many companies still fail to fulfill their environmental responsibilities adequately. The purpose of this study is to examine the influence of Environmental Evaluation and Material Flow Cost Accounting on Sustainable Development. The approach adopted focuses on numerical aspects, with the research concentrating on companies in the basic and chemical industries listed on the Indonesia Stock Exchange during the period 2020-2022. The sampling method used is purposive sampling, resulting in a sample size of 75 (25 companies over 3 years). SmartPLS 3 is employed as the analytical tool. The research findings indicate that environmental evaluation has no significant impact, whereas material flow cost accounting has a substantial impact on sustainable development. These findings bear important implications for further research to enrich the investigated factors and consider more representative samples to enhance their impact on Sustainable Development, requiring more effective approaches to be considered.